2005
DOI: 10.1007/s11249-004-2752-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved nanoscale chemical and mechanical characterization of ZDDP antiwear films on aluminum?silicon alloys under cylinder/bore wear conditions

Abstract: Understanding the lubrication of aluminum-silicon (Al-Si) alloys (>18% Si) under conditions similar to those in the cylinder/bore system is vital to determining their applicability to current engine designs. A novel investigation of the location of zinc-dialkyl-dithiophosphate (ZDDPs) antiwear (AW) film formation on an Al-Si alloy has been performed using X-ray absorption near edge structure (XANES) analysis, X-ray photoelectron emission spectroscopy (X-PEEM), and imaging nanoindentation techniques. A study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 65 publications
13
58
1
Order By: Relevance
“…The FIB-SIMS mapping clearly showed regions of preferential Zn and Mo rich layers dissociated on silicon and matrix respectively, although as shown from the depth profiles in Figure 8 this was not exclusively the case, with small amounts of Mo on Si and Zn in the matrix. This was broadly consistent with work by Nicholls et al [34,36,37] who used a number of X-Ray techniques (XANES, X-PEEM) to determine the mechanism of preferential long chain poly-phosphate anti-wear pad formation from ZDDP additives at contacting Si interfaces. The presence of iron was also noted on the contact surface of the Si particles, Figure 5 d), and would be consistent with the theory that a ferrous oxide surface is necessary to allow desorption of Zn based additives prior to formation of a glassy phosphate anti-wear pad [19,31,34,36,38].…”
Section: Friction Behavioursupporting
confidence: 87%
“…The FIB-SIMS mapping clearly showed regions of preferential Zn and Mo rich layers dissociated on silicon and matrix respectively, although as shown from the depth profiles in Figure 8 this was not exclusively the case, with small amounts of Mo on Si and Zn in the matrix. This was broadly consistent with work by Nicholls et al [34,36,37] who used a number of X-Ray techniques (XANES, X-PEEM) to determine the mechanism of preferential long chain poly-phosphate anti-wear pad formation from ZDDP additives at contacting Si interfaces. The presence of iron was also noted on the contact surface of the Si particles, Figure 5 d), and would be consistent with the theory that a ferrous oxide surface is necessary to allow desorption of Zn based additives prior to formation of a glassy phosphate anti-wear pad [19,31,34,36,38].…”
Section: Friction Behavioursupporting
confidence: 87%
“…The study of Al-Si alloys against steel lubricated by commercial engine oils under boundary lubrication conditions has been reported occasionally since the 1960s and 1970s [2,3], with research focused mainly on the tribological performance of Al-Si alloys lubricated by zinc dialkyl dithiophosphate (ZDDP) [4][5][6]. The challenge in understanding fully these interactions lie mainly in the research being performed using different Al-Si alloys and under different testing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Performance of this additive in maintaining low wear is due to its interaction with the ferrous material resulting in formation of a layered phosphate/sulphide tribofilm at the interface. Formation of the ZDDP tribofilm in Al-Si alloys has been recently studied [4][5][6] and, although the findings are still not conclusive, an insight on the interaction between this additive and the Al-Si alloy has started to develop. It is demonstrated that polyphosphates form on both Al and Si material [6] while the higher Si content promotes formation of the polyphosphates from the ZDDP additive [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, micro-scale variations in chemical composition may also be expected to a↵ect the tribofilm thickness on a similar scale. It has been shown that for Al-Si based alloys, which consist of Al-and Si-rich phases, under certain conditions tribofilm is preferentially formed on harder Si-rich phases in contrast to softer Al-rich phases [31]. In a study of ZDDPderived tribofilm on an Al-Si alloy performed with the use of various chemical micro-analysis techniques, Nicholls et al [31] attributed this e↵ect to the increased contact pressure, to which Si-rich precipitates are exposed, as these were shown to protrude by about 150 nm from the Al-rich matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for Al-Si based alloys, which consist of Al-and Si-rich phases, under certain conditions tribofilm is preferentially formed on harder Si-rich phases in contrast to softer Al-rich phases [31]. In a study of ZDDPderived tribofilm on an Al-Si alloy performed with the use of various chemical micro-analysis techniques, Nicholls et al [31] attributed this e↵ect to the increased contact pressure, to which Si-rich precipitates are exposed, as these were shown to protrude by about 150 nm from the Al-rich matrix. Xia et al [32] have noted that when oil containing ZDDP and a low concentration of molybdenum dialkyldithiocarbamate (MoDTC) is used to lubricate Al-Si alloy -cast iron tribocouples, it results in more pronounced wear of the Al-matrix with respect to hard Si-rich phase.…”
Section: Introductionmentioning
confidence: 99%